A small, elderly dragon - Keller, Beverly; Malone, Nola Langner (New York Lothrop, Lee & Shepard, 1984)
When the kingdom is overtaken by a sorcerer, young Princess Dorma, nearsighted and awkward, helps a small, elderly dragon find the power needed to save the villagers.
Keywords: Children's stories, American; Dragons -- Fiction; Princesses -- Fiction; Fantasy